From mechanisms to precision medicine: the role of organoids in studying the gut microbiota-tumor microenvironment axis - Zheng, Si-yang; Su, You-yu; Cai, Fu-liang; Xu, Da-fang; Xu, Yong-qiang (Frontiers in Microbiology, 2025)
Intestinal organoids are three-dimensional in vitro models derived from patient-specific tissues, which can recapitulate the structural and functional characteristics of the native intestinal epithelium, including interactions with the gut microbiota. In the study of host-microbiota crosstalk within the context of the Tumor Microenvironment (TME), they have become highly effective tools, providing an opportunity to explore the role of microorganisms in carcinogenic processes, immune regulation, and therapeutic responses. Although organoids can successfully simulate key aspects of the TME, certain features—such as systemic immune interactions, neuroendocrine axes, and dynamic microbial communities—remain difficult to fully replicate. This review primarily covers the advances in organoids applied to the research of the microbiota-TME axis, examines their current limitations, and further advocates for their integration with multi-omics and organ-on-a-chip technologies to enhance physiological relevance and the value of translational applications.